2022
DOI: 10.1111/nuf.12817
|View full text |Cite
|
Sign up to set email alerts
|

The perception of shared governance and engagement in decision‐making among nurses

Abstract: Background Shared governance is a structural framework for operationalizing nursing ownership and accountability for nursing practice. Healthcare institutions are striving to promote healthy and satisfactory work conditions to retain their qualified personnel and achieve organizational stability and high care quality. However, little is known about nurses' participation in governance in developing countries. Aim This study aims to evaluate the levels of shared governance, also known as professional governance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…The current results might be explained by the fact that bedside nurses believe that pressure ulcers incident should be reported all the times (regardless its degree) because it is a frequent and common issue in all clinical settings all over the world that is given higher priority in hospital education programs than confidentiality problems. Plus, many nurses perceive a pressure ulcer incident as an indicator of poor quality of care rather than a system failure, which requires the nurses to make quick decision-making [ 41 , 42 ]. Moreover, this result is slightly consistent with the results of AbuAlRub et al, in which they found that around 45% of the surveyed nurses believed that they should report an incident of “breach in confidentiality” at all times [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current results might be explained by the fact that bedside nurses believe that pressure ulcers incident should be reported all the times (regardless its degree) because it is a frequent and common issue in all clinical settings all over the world that is given higher priority in hospital education programs than confidentiality problems. Plus, many nurses perceive a pressure ulcer incident as an indicator of poor quality of care rather than a system failure, which requires the nurses to make quick decision-making [ 41 , 42 ]. Moreover, this result is slightly consistent with the results of AbuAlRub et al, in which they found that around 45% of the surveyed nurses believed that they should report an incident of “breach in confidentiality” at all times [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A utilização bem-sucedida da governança compartilhada resulta no crescimento profissional, no aumento da competência de liderança em enfermagem e na melhoria da qualidade. A ideia principal da governança compartilhada é que o uso do poder e a tomada de decisões devem ser feitos no lugar certo, na linha de frente no local de prestação de cuidados, onde os cuidados são realizados (JABER A, et al, 2022. Estudos brasileiros sobre governança em saúde e enfermagem são incipientes e não contemplam aspecto relativo à implementação da governança compartilhada como um modelo de gestão de enfermagem para as organizações de saúde (SANTOS JLG, 2014).…”
Section: Introductionunclassified